Top of the lake - Bradshaw, Mark (BBC Video, 2013)
A pregnant 12 year-old girl who won't reveal who the father is, walks chest deep into the freezing waters of a New Zealand lake and disappears. Robin Griffin is called in to investigate and becomes more and more obsessed. As she searches, she slowly begins to realize that finding the girl is tantamount to finding herself, a self she has kept well hidden. A powerful and haunting story about our search for happiness, where the dream of paradise attracts its dark twin, the fall